Respuestas
Respuesta dada por:
38
3x + 9 = 25 - 25
3x + 9 = 0
3x = 0 - 9
3x = -9
x = -9 : 3
x = - 3
Comprobamos:
3x + 9 =
3. -3 + 9 =
-9 + 9 =
0 ( 25 - 25 = 0)
3x + 9 = 0
3x = 0 - 9
3x = -9
x = -9 : 3
x = - 3
Comprobamos:
3x + 9 =
3. -3 + 9 =
-9 + 9 =
0 ( 25 - 25 = 0)
Respuesta dada por:
28
La ecuación que tienes es:
3x + 9 = 25 - 25
3x + 9 = 0
3x = - 9
x = - 9/3
x = - 3
Respuesta.
x = - 3
3x + 9 = 25 - 25
3x + 9 = 0
3x = - 9
x = - 9/3
x = - 3
Respuesta.
x = - 3
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años